Peran Mahasiswa KKN dalam Pengembangan Berwirausaha melalui Pendidikan Kewirausahaan - Diana Wangania; Christian Tarandung; Mei Hastuti; Hendry Rumengan; Hartati Umar; Angely Sondakh; Frangky Robial; Henny Tumbelaka; Yudith Rondonuwu; Doly Tiagas (Jurnal Kemitraan Masyarakat, 2024)
This activity aims to increase student involvement and role in entrepreneurial activities as well as foster students' interest in entrepreneurship through entrepreneurship education through marketing and product sales strategies. This activity shows that students' entrepreneurial interest is very high, the marketing and sales skills demonstrated are the main reference in developing their ideas for business. So, this activity shows how to develop through training strategies towards product sales simulations and group work carried out by students. The student's role in developing this strategy succeeded in significantly improving marketing and sales skills. The results of this entrepreneurial practice provide valuable insight for students regarding the factors and keys to success in entrepreneurship.